DEVELOPMENT OF PROBLEM-BASED LEARNING-BASED MATHEMATICS WITH THE ASSISTANCE OF GEOGEBRA APPLICATIONS TO IMPROVE STUDENTS' MATHEMATICAL CONCEPTS UNDERSTANDING ABILITY - Najwah Rokan; Putri Elmania; Feri Gunawan Sihombing; Asiatul Mardiah Hasibuan; Nur Rahmi Rizqi; Nur Rahmi Rizqi (JURNAL EDUSCIENCE, 2023)
This research is a development research (R & D) that aimsÂ toÂ improve students' ability to understand mathematical concepts with learning media assisted byÂ problem-based learningÂ geogebra applications.Â  The benefit of this research is that students can foster their learning interest in learning mathematics with the help of geogebra application technology so that students can be active in learning and think logically and broadly. This research uses a developmentÂ researchÂ methodÂ with a "Four-D Model" or 4-D model which includes four stagesofÂ development, namely:Â define,Â design,Â developÂ andÂ disseminate.Â aÂ process to develop and validate a product (Sugiyono, 2019: 394).Â Meanwhile, according to Sariani, the results of learning media development explained geogebra-assisted learning materials, lesson implementation plans (RPP), teacher books (BG), student books (BS), group worksheets (LKK), concept comprehension ability test instruments, and mathematical disposition questionnaires.Â OutÂ of 38 students, 5 students were incomplete with a completeness rate ofÂ 20% and 33 students were incomplete with a completeness rate of 80%.Â For students who are more motivated, have a deeper understanding, and have better math skills.Â Development instrument reaction form sheets, learning program drafts, and student works Student questionnaires and knowledge tests of mathematical concepts are also given on stage.Â Once the production and assessment of teaching materials and mathematical instruments is complete, validators will proceed to validate previously discontinued instruction, math, and instrumentation use evaluation sheets.Â Student answer questionnaires and worksheets using learning media such as GeoGebra were used to assess students' understanding of mathematical topics at intervals 2.5â€“Mâ€“3.5 with valid categories.Keywords:Â Geogebra, Problem Based Learning , Understand Mathematical ConceptsÂ Abstrak Penelitian ini merupakan penelitian pengembangan (R&D) yang bertujuan untuk meningkatkan kemampuan pemahaman konsep matematis siswa dengan media pembelajaran berbantuan aplikasi geogebra berbasis problem based learning. Manfaat penelitian ini adalah agar siswa dapat menumbuhkan minat belajar meraka dalam pembelajaran matematika dengan bantuan teknologi aplikasi geogebra agar siswa dapat aktif dalam pembelajaran dan berfikir logis serta luas. Â Penelitian ini menggunakan metode penelitian pengembangan dengan â€œFour-D Modelâ€ atau model 4-D yang meliputi empat tahap pengembangan yaitu: define (pendefinisian), design (perancangan), develop (pengembangan) dan disseminate (penyebaran). suatu proses untuk mengembangkan dan memvalidasi suatu produk (Sugiyono, 2019). Sedangkan menurut Sariani, , Hasil Pengembangan Media Pembelajaran Dijelaskan materi pembelajaran berbantuan geogebra, rencana pelaksanaan pembelajaran (RPP), buku guru (BG), buku siswa (BS), lembar kerja kelompok (LKK), instrumen tes kemampuan pemahaman konsep, dan angket disposisi matematis. Bahwa dari 38 siswa, 5 siswa tidak tuntas dengan tingkat ketuntasan 20% dan 33 siswa tidak tuntas dengan tingkat ketuntasan 80%. Untuk siswa yang lebih termotivasi, memiliki pemahaman yang lebih dalam, dan memiliki kemampuan matematika yang lebih baik. Lembar formulir reaksi instrumen pengembangan, draf program pembelajaran, dan karya siswa Kuesioner siswa dan tes pengetahuan konsep matematika juga diberikan di atas panggung. Setelah produksi dan penilaian bahan ajar dan instrumen matematika selesai, validator akan melanjutkan untuk memvalidasi lembar evaluasi penggunaan instruksi, matematika, dan instrumentasi yang sebelumnya dihentikan. Angket jawaban siswa dan lembar kerja menggunakan media pembelajaran seperti GeoGebra digunakan untuk menilai pemahaman siswa terhadap topik matematika pada interval 2,5â€“Mâ€“3,5 dengan kategori valid.Kata Kunci: Geogebra, Problem Based Learning, Pemahaman Konsep Matematis